Recent CP violation and lifetime results from CMS - Sergeychik Vladimir (EPJ Web of Conferences)
Recent results on CP violation in charm and beauty sector, as well as lifetime measurements, by the CMS experiment at the LHC are presented. The first measurement of CP violation in charm by CMS is reported, as well as the most precise measurement of effective lifetime τ(Bs0→J/ψKS0)$${\tau (B_s^0 \to J/\psi K_S^0)} $$ and the first evidence for CP violation in the Bs0$${B_s^0} $$ → J/ψ ϕ(1020) → μ+ μ−K+K− decay. The analyses are based on 13 TeV proton-proton collision data.